Congenital hyperplastic goitre in a goat - Sheikh Omar, Abdul Rahman (Persatuan Doktor Veterinar Malaysia, 1985)
A case of congenital hyperplastic goitre in a three-day old kid of Kambing- Katjang breed is reported.